Conciliarism a history of decision-making in the church - Valliere, Paul. (New York : Cambridge University Press, 2012)
"Conciliarism is one of the oldest and most essential means of decision-making in the history of the Christian Church. Indeed, as a leading Orthodox theologian Alexander Schmemann states, 'Before we understand the place and the function of the council in the Church, we must, therefore, see the Church herself as a council.' Paul Valliere tells the story of councils and conciliar decision-making in the Christian Church from earliest times to the present. Drawing extensively upon the scholarship on conciliarism which has appeared in the last half-century, Valliere brings a broad ecumenical perspective to the study and shows how the conciliar tradition of the Christian past can serve as a resource for resolving conflicts in the Church today. The book presents a conciliarism which involves historical legacy, but which leads us forward, not backward, and which keeps the Church's collective eyes on the prize - the eschatological kingdom of God"--
Machine generated contents note: Introduction; 1. The conciliar testament; 2. The conciliar tradition; 3. The conciliar theory; 4. Conciliarism in Anglican experience; 5. The Pan-Anglican Council; Conclusion; Bibliography.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Conciliar theory -- History; RELIGION / Christian Church / History; RELIGION / Christian Theology / Ecclesiology; Electronic books